Perfect romancestoryline in novel versus film adaptation (a case study of 'Ombak Rindu’) / Nurul Azira Syuhada Ismail, Nur Atiqah Syahirah Musi Ismail and Mohamad Al As Mohd Yunos - Ismail, Nurul Azira Syuhada; Ismail, Nur Atiqah Syahirah Musi; Mohd Yunos, Mohamad Al As
Book-to-film adaptation has been a trend in both local and international film markets. This choice might lead to issues such as lack of originality in the film, only relying on original literature for its inspiration. The trend of producing a book-to-film adaptation in Malaysia have been increasing from year to year. Thus, the purpose of doing this research is to identify on the rating of readers and viewers of novel and film Ombak Rindu. The novel of Ombak Rindu was published in year 2002 while the film was released by the end of 2011, directed by Osman Ali. The data has been collected from six female students from the Diploma of Faculty of Communication and Media Studies in Universiti Teknologi MARA (UiTM) Kampus Rembau. The students were divided into two categories; the reader and viewer of Ombak Rindu respectively. The researcher wants to find out whether the novel or its film adaptation is rated higher by their own readers and viewers. The method used in this research is qualitative which in-depth interview is conducted involving the respondents.